Active Reconnecting Learning Strategies to Increase Student Interest and Active Learning - Wijaya, Hengki; Darmawan, I Putu Ayub; Setiana, Suzana Claudia; Helaluddin, Helaluddin; Weismann, Ivan Th. J. (Indonesian Journal of Instructional Media and Model, 2021)
The main issue of education in the last few decades is the efforts and solutions in improving the quality of teaching and learning. In this case, the teacher’s steps are to conduct classroom action research, which is a form of a bottom-up approach in improving the quality of education. This action research introduces active reconnecting learning strategies for increasing student interest and learning activities. The CAR design includes three stages, namely the pre-cycle, cycle 1, and Cycle 2. Some of the instruments used in this study are checklist observation sheets, questionnaires, and learning outcomes tests, which are then analyzed using quantitative approaches. The results showed that this strategy was proven to improve student learning outcomes, interests, and activeness. Student learning interest increased from 59.35 to 65.5 in cycle 1 and 80.5 in cycle 2. Likewise, student learning activeness observations increased with the highest percentage on one indicator from 25% (pre-cycle) to 80% and 90% (cycle 1 and 2). Student learning outcomes have also increased from an average grade of 60 in the pre-cycle phase to 74.25 (cycle 1). And it rose again to 80 in cycle 2.